Beliefs about Aging and Implications for Future Educational Programming in Kansas - Sellers, Debra M.; Bolender, Benjamin C; Crocker, Andrew B. (My University, 2010)
The specific aim of this research study was to gain knowledge regarding beliefs about aging, in order to develop future, priority, educational, and aging-related opportunities in Kansas. The study included six focus groups with a self-selected sample of Kansans born during the years 1946-1964 (N = 39). Data were analyzed through utilization of open and focused coding processes. The main themes that surfaced included: health is fundamental, communities and families provide assistance, personal experiences shape perceptions, and American society creates expectations. Educational programs that were indicated as priority areas for future development and implementation are discussed.
Keywords: Educational gerontology; Aging education; Educational change; Beliefs; Focus groups; Community support